The Effect of Moringa oleifera on Pregnant Women and Breastfeeding Mothers toward Social-personal Development of Children Aged 18–23 Months in Jeneponto, South Sulawesi - Hastuti, Hastuti; Hadju, Veni; Citrakesumasari, Citrakesumasari; Maddeppungeng, Martira; Tanziha, Ikeu; Saleh, Aryanti; Sari, Karmila (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Insufficient nutrition intake at the age of <2 years has an impact on decreasing physical growth and development. AIM: Analyzing the effect of giving Moringa leaves on pregnant women and breastfeeding mothers toward the social development of children aged 18–23 months in Jeneponto, South Sulawesi. METHODS: This study was a longitudinal study after supplementation for pregnant women and breastfeeding mothers with Moringa oleifera or folic acid, and iron. Research subjects were children whose was monitored from the age of 18–23 months in Jeneponto District. The number of samples that met the inclusion criteria at the age of 23 months was 344 children. The sample was divided into three groups: A group of children of mothers who got Moringa leaf powder supplements, iron-folic acid supplements, and Moringa leaf extract. Child development was measured using the denver development screening test. Data were analyzed statistically with Chi-square. RESULTS: There were 107 children (91.5%) with normal social-personal development in the Moringa leaves powder (MLP) group. This number was more than the children in the iron folic acid (IFA) group of 103 children (86.6%) and the Moringa leaves extract (MLE) group of 95 children (88.0%). Differences were also found in the social-personal development of children who were suspect in the IFA group more than children who were suspect in the MLP group or the MLE group. CONCLUSION: There was no significant difference in children’s social-personal development between the three study groups.